POTASSIUM-INTERCALATED MANGANESE DIOXIDE AS LITHIUM-ION BATTERY CATHODES: A DENSITY FUNCTIONAL THEORY STUDY - Agus Ismail; Herry Agung Prabowo; Muhammad Hilmy Alfaruqi (SINERGI, 2019)
It is obvious to harness the intermittent renewable energy resources, energy storage applications, such as a lithium-ion battery, are very important. α‒type MnO2 is considered as an attractive cathode material for lithium-ion battery due to its relatively large (2 × 2) tunnel structure, remarkable discharge capacity, low cost, and environmental benignity. However, low intrinsic electronic conductivity of α‒type MnO2 limits its full utilization as a cathode for a lithium-ion battery. Therefore, studies to enhance the α‒type MnO2 properties are undoubted of great interest. While previous computational studies have been focused on pristine α‒type MnO2, in the present report, we present the theoretical research on potassium-intercalated α‒type MnO2 using first principle Density Functional Theory calculations for the first time. Our results showed that potassium-intercalated α‒type MnO2 improved the electronic conductivity which beneficial for energy storage application. The structural transformation of potassium-intercalated α‒type MnO2 upon lithium insertion are also discussed. Our results may open the avenue for further utilization of potassium-intercalated α‒type MnO2 materials for not only the lithium-ion battery but also other type energy storage systems.